Topic - Review of Cloud Computing in Fault Tolerant Environment With Efficient Energy Consumption (International Journal of Scientific Research and Management (IJSRM), 2013)
In this research paper, the exhaustive study has been done on fault tolerance in cloud, fault tolerance’s types, limitations are introduced. Further, if fault tolerance is implemented then how much dependable it would be for the real time applications. When multiple instances of an application are running on several machines and one of the machine goes down, there is a need to implement an autonomic fault tolerance technique that can handle such types of faults. The Median Absolute Deviation (MAD) is a measure of statistical dispersion and is more robust estimator of scale than the sample variance or standard deviation, as it behaves better with distributions without a mean or variance and being more resilient to outliers in a data set than the standard deviation.There were various tools like Hadoop, Azzure, HAproxy etc via which fault tolerance can be applied. Scheduling is one of the very important components which can be used to detect performance on the cloud.